Risk factors in patients with non-alcoholic fatty liver disease associated with arterial hypertension, overweight and obesity - Yu. A. Nikolaev; E. V. Sevostyanova; V. Ya. Polyakov; I. M. Mitrofanov; A. A. Us (Сибирский научный медицинский журнал, 2020)
Purpose of the study was to investigate the features of the occurrence of risk factors in patients with non-alcoholic fatty liver disease associated with arterial hypertension, overweight and obesity.Material and methods. The object of the study was the data of 14 393 case histories of patients with arterial hypertension (AH), non-alcoholic fatty liver disease (NFLD), overweight body (OB) and obesity, examined and treated at the clinic of the Federal Research Center forFundamental and Translational Medicine (Novosibirsk).Results and discussion. Features of biochemical parameters in patients with NFLD with AH, OB and obesity were studied in comparison with patients with isolated diseases. It was shown that in patients, in case of the presence of this comorbidity, the value of transsystem polymorbidity is statistically significantly increased compared with groups of patients with isolated diseases. It was established that patients with concomitant diseases have higher, statistically significant values of systolic and diastolic blood pressure, body mass index. They have higher concentrations of total cholesterol, triglycerides, high density lipoprotein cholesterol, glucose, uric acid in the blood serum, higher atherogenic index. A study of the frequency of occurrence of risk factors in the groups showed the highest frequency values in patients with associated diseases: high blood pressure, dyslipidemia, hypertriglyceridemia, hypercholesterolemia, hypoalphacholesterolemia, hyperlipidemia, increased atherogenic index, hyperglycemia, hyperuricemia, the higher levels of C-reactive protein, which indicates that with associated pathology, changes in carbohydrate, lipid and purine metabolism are more pronounced. These changes are factors that aggravate the course of the pathology and are risk factors for the development of diabetes mellitus, atherosclerosis and associated conditions, which requires a personalized approach to the treatment and prevention of this category of patients. The results of this study can form the basis for the development of new medical technology for assessing the severity of condition in patients with non-alcoholic fatty liver disease combined with arterial hypertension, overweight and obesity.